A dual‐chamber method for quantifying the effects of atmospheric perturbations on secondary organic aerosol formation from biomass burning emissions. Issue 11 (10th June 2017) - Tkacik, Daniel S.; Robinson, Ellis S.; Ahern, Adam; Saleh, Rawad; Stockwell, Chelsea; Veres, Patrick; Simpson, Isobel J.; Meinardi, Simone; Blake, Donald R.; Yokelson, Robert J.; Presto, Albert A.; Sullivan, Ryan C.; et al.
Abstract: Biomass burning (BB) is a major source of atmospheric pollutants. Field and laboratory studies indicate that secondary organic aerosol (SOA) formation from BB emissions is highly variable. We investigated sources of this variability using a novel dual‐smog‐chamber method that directly compares the SOA formation from the same BB emissions under two different atmospheric conditions. During each experiment, we filled two identical Teflon smog chambers simultaneously with BB emissions from the same fire. We then perturbed the smoke with UV lights, UV lights plus nitrous acid (HONO), or dark ozone in one or both chambers. These perturbations caused SOA formation in nearly every experiment with an average organic aerosol (OA) mass enhancement ratio of 1.78 ± 0.91 (mean ± 1 σ ). However, the effects of the perturbations were highly variable ranging with OA mass enhancement ratios ranging from 0.7 (30% loss of OA mass) to 4.4 across the set of perturbation experiments. There was no apparent relationship between OA enhancement and perturbation type, fuel type, and modified combustion efficiency. To better isolate the effects of different perturbations, we report dual‐chamber enhancement (DUCE), which is the quantity of the effects of a perturbation relative to a reference condition. DUCE values were also highly variable, even for the same perturbation and fuel type. Gas measurements indicate substantial burn‐to‐burn variability in the magnitude and composition of SOA precursor emissions, even in repeated burns of the same fuel under nominally identical conditions. Therefore, the effects of different atmospheric perturbations on SOA formation from BB emissions appear to be less important than burn‐to‐burn variability. Key Points: Perturbing biomass burning (BB) emissions with UV, UV + HONO, and dark ozonolysis in a smog chamber creates secondary organic aerosol (SOA) The amount of SOA formation from biomass smoke is highly variable Burn‐to‐burn differences in the composition of BB emissions cause more variability in SOA production than different atmospheric perturbations